The duchess deal eaudiobook - Dare, Tessa (Girl Meets Duke, 2017)
When girl meets Duke, their marriage breaks all the rules... Since his return from war, the Duke of Ashbury's to-do list has been short and anything but sweet: brooding, glowering, menacing London ne'er-do-wells by night. Now there's a new item on the list. He needs an heir—which means he needs a wife. When Emma Gladstone, a vicar's daughter turned seamstress, appears in his library wearing a wedding gown, he decides on the spot that she'll do. His terms are simple: - They will be husband and wife by night only. - No lights, no kissing. - No questions about his battle scars. - Last, and most importantly... Once she's pregnant with his heir, they need never share a bed again. But Emma is no pushover. She has a few rules of her own: - They will have dinner together every evening. - With conversation. - And unlimited teasing. - Last, and most importantly... Once she's seen the man beneath the scars, he can't stop her from falling in love...